Effects of vitamin D supplementation on metabolic parameters in women with polycystic ovary syndrome: a randomized controlled trial - Xinling Wen; Li Wang; Fen Li; Xuewen Yu (BMC, 2024)
Abstract Objective The aim of this study was to explore the effects of vitamin D supplementation on metabolic parameters in women with polycystic ovary syndrome (PCOS). Methods A total of 60 PCOS women with vitamin D deficiency or insufficiency were enrolled in this randomized controlled trial. Participants were randomized to vitamin D group (2000 IU/day) or control group. The observational parameters were measured at baseline and after treatment, including body mass index (BMI), waist to hip ratio (WHR), oral glucose tolerance test (OGTT) and insulin release test, and lipid metabolism parameters. Results The serum 25(OH)D concentrations at different time points after vitamin D supplementation were significantly higher than that in control group (P < 0.05). The BMI, WHR, insulin concentrations, homeostasis model assessment of insulin resistance (HOMA-IR), triglycerides (TG), total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C) concentrations in women of Vitamin D group after 12 weeks of treatment were significantly lower than that in women of control group (P < 0.05). The serum insulin concentrations and HOMA-IR at different time points of OGTT, serum TG, TC and LDL-C concentrations in women of vitamin D group (obesity) were significantly lower compared with control group (obesity) (P < 0.05). The BMI, WHR, TG, TC and LDL-C concentration in women of vitamin D group (IR) were significantly lower compared with control group (IR) (P < 0.05). No significant difference was observed in metabolic parameters between vitamin D group (non-obesity) and control group (non-obesity) (P > 0.05), and these differences of metabolic parameters were also not observed between vitamin D group (non-IR) and control group (non-IR) (P > 0.05). Conclusion Vitamin D supplementation had beneficial effects on metabolic parameters in PCOS women, especially in women with obesity or insulin resistance.